(untitled) (Transactions of the Association of European Schools of Planning, 2021)
Predicting the future is a difficult and inexact business and, generally, humans are more prone to focus on immediate problems and short-term problem-solving rather than long-range planning. In fact, long-range forecasts are tricky and often rendered wrong due to catalytic events. The dramatic changes in teaching, learning, and conducting research that have seemingly catapulted Higher Education (HE) institutions into a new modus operandi over the past 24 months are a case in point. Who would have predicted that higher education would be conducted by a great many institutions almost entirely virtually and over sustained amounts of time? That academics would teach from their homes lecturing to a screen of black boxes and images? That students would do fieldwork virtually via video, embedded questions and tasks, and that the practice of research teams discussing progress and findings in person would practically vanish?